SOCIAL AND POLITICAL LIFE IN THE PERIOD OF MUHAMMAD PORSO - Munisxon Gulamova (Galaxy International Interdisciplinary Research Journal, 2022)
This article reflects the socio-political life of the era of Khoja Muhammad Porso.